Analisis Resepsi Siswa SMK Perguruan Cikini terhadap Kenakalan Remaja dalam Serial Extracurricular - Siti Sarah; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Juvenile delinquency is a problem that is rife. Juvenile delinquency cases continue to increase both in terms of quantity and quality. Initially, adolescent behavioral deviations were in the form of cheating, truancy and smoking. But now it has been transformed into criminal behavior such as brawl, working in the world of prostitution, narcotics abuse, and free sex. This study uses Stuart Hall's encoding-decoding theory with a constructivism paradigm and a descriptive qualitative approach. The active audience in this study were students of SMK Perguruan Cikini. The meaning by the audience or the decoding process occurs using the frame of reference and the field of experience that is owned. Like the juvenile delinquency shown in the Extracurricular series. The results of this study indicate that there are differences in the meaning of each informant regarding juvenile delinquency committed by high school students in the Extracurricular series. In adolescence who are still unstable, it is easy for teenagers to fall into negative things. Many factors influence the occurrence of juvenile delinquency, such as economic factors, lack of parental supervision, and adverse environmental influences.